1999
DOI: 10.1056/nejm199908053410604
|View full text |Cite
|
Sign up to set email alerts
|

Gemfibrozil for the Secondary Prevention of Coronary Heart Disease in Men with Low Levels of High-Density Lipoprotein Cholesterol

Abstract: Gemfibrozil therapy resulted in a significant reduction in the risk of major cardiovascular events in patients with coronary disease whose primary lipid abnormality was a low HDL cholesterol level. The findings suggest that the rate of coronary events is reduced by raising HDL cholesterol levels and lowering levels of triglycerides without lowering LDL cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
1,444
3
40

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 3,140 publications
(1,534 citation statements)
references
References 36 publications
28
1,444
3
40
Order By: Relevance
“…Epidemiological, biological, and genetic studies have provided robust evidence of a strong association between elevated TG levels and higher rates of CV events 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. Furthermore, TG reduction lowers several inflammatory markers associated with CV risk, and subgroup and post hoc analyses of outcome studies suggest possible reductions in major CV events with TG‐lowering therapy 3, 4, 5, 6, 7, 8, 9, 10, 11.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological, biological, and genetic studies have provided robust evidence of a strong association between elevated TG levels and higher rates of CV events 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. Furthermore, TG reduction lowers several inflammatory markers associated with CV risk, and subgroup and post hoc analyses of outcome studies suggest possible reductions in major CV events with TG‐lowering therapy 3, 4, 5, 6, 7, 8, 9, 10, 11.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological, biological, and genetic studies have provided robust evidence of a strong association between elevated TG levels and higher rates of CV events 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. Furthermore, TG reduction lowers several inflammatory markers associated with CV risk, and subgroup and post hoc analyses of outcome studies suggest possible reductions in major CV events with TG‐lowering therapy 3, 4, 5, 6, 7, 8, 9, 10, 11. Finally, studies administering higher‐dose EPA suggest additional beneficial effects beyond lipid‐lowering that may be unique to EPA relative to other TG‐lowering therapies, such as beneficial changes in coronary plaque characteristics, which may lead to reductions in major CV events 4, 16, 25, 26, 27, 28, 29, 30, 31, 32, 33…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 A recent angiographic study has indicated that antioxidant supplementation to lipid-lowering therapy prevented HDL-C elevation and was associated with a worse coronary angiographic outcome; 28,29 conversely, a predominant increase of HDL-C by gemfibrozil without a major reduction in LDL-C levels was associated with a significant reduction in the rate of coronary events. 30 Finally, patients with low HDL-C benefitted most when treated with fluvastatin in the Lipoprotein and Coronary Atherosclerosis Study (LCAS). 31 No association was seen between changes in plasma lipids during statin therapy and individual SNPs, supporting our findings that the interaction of multiple CETP SNPs within a haplotype is a more powerful determinant of the clinical phenotype than are individual SNPs.…”
Section: Discussionmentioning
confidence: 99%